2018
DOI: 10.1108/ebhrm-10-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender and profit margin on the duration of hiring process for professional service firms

Abstract: Purpose The purpose of this paper is to explore the impact of recruiter gender and profit margin on the duration of the hiring process in professional services firms (PSFs). Design/methodology/approach In evaluating over 500 recruiting transactions in a PSF, a factorial ANOVA was performed to determine if there is a significant interaction between recruiter gender and profit margin on days it take to fill an open position. Findings The results suggest a significant interaction exists between the recruiter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…IEIE, CRDR and quick ratio (QR) reduced the profitability of public banks in India, while cash deposit ratio (CDR) and Advances to Loan Funds (ALF) increased the effectiveness of public banks, and under the total banks IEIE, CRDR reduced the profitability, on the other side, CDR, ALF and Total Debt to Owners Fund (TDOF) increased the profitability of total banks in India, and finally under the dependency of ROA, CRDR and TDOF reduced the return of private banks in India, while CDR, ALF and QR enhanced the profitability of private banks (Bansal et al, 2018). Agrawal et al (2018) found a significant interaction exists between the recruiter gender and profit margin variables in effect on days that it takes to fill an open position, and at lower job position profit margins, female recruiters were found to outperform their male counterparts, conversely, at higher job position profit margins, male recruiters appear to outperform female recruiters. Hyun (2017) investigates the effect of the 1997 Korean financial crisis on the trade credit behavior of Korean small and medium sized enterprises (SMEs) using a unique panel data set for the period 1994 to 1999 and uncover new evidence supporting the substitution and redistribution hypotheses, which contradicts earlier studies, specifically, the results show that liquid SMEs provided more trade credit to their client firms during the credit contraction, while financially constrained SMEs received more trade credit from their suppliers, further, evidence found that SMEs in financially distressed regions relied more on trade credit than their counterparts in financially healthier regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IEIE, CRDR and quick ratio (QR) reduced the profitability of public banks in India, while cash deposit ratio (CDR) and Advances to Loan Funds (ALF) increased the effectiveness of public banks, and under the total banks IEIE, CRDR reduced the profitability, on the other side, CDR, ALF and Total Debt to Owners Fund (TDOF) increased the profitability of total banks in India, and finally under the dependency of ROA, CRDR and TDOF reduced the return of private banks in India, while CDR, ALF and QR enhanced the profitability of private banks (Bansal et al, 2018). Agrawal et al (2018) found a significant interaction exists between the recruiter gender and profit margin variables in effect on days that it takes to fill an open position, and at lower job position profit margins, female recruiters were found to outperform their male counterparts, conversely, at higher job position profit margins, male recruiters appear to outperform female recruiters. Hyun (2017) investigates the effect of the 1997 Korean financial crisis on the trade credit behavior of Korean small and medium sized enterprises (SMEs) using a unique panel data set for the period 1994 to 1999 and uncover new evidence supporting the substitution and redistribution hypotheses, which contradicts earlier studies, specifically, the results show that liquid SMEs provided more trade credit to their client firms during the credit contraction, while financially constrained SMEs received more trade credit from their suppliers, further, evidence found that SMEs in financially distressed regions relied more on trade credit than their counterparts in financially healthier regions.…”
Section: Literature Reviewmentioning
confidence: 99%